2013
DOI: 10.1038/aja.2013.81
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of sperm DNA fragmentation and sperm high-magnification for predicting outcome of assisted reproduction treatment

Abstract: Over the last years, major improvements in the field of male infertility diagnosis have been achieved. The aim of this study was to determine the diagnostic usefulness of sperm DNA integrity and sperm vacuolisation for predicting outcome in infertile couples undergoing in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI) treatments. A cohort study from 152 infertile couples undergoing sperm DNA fragmentation and high-magnification tests prior to an assisted reproduction treatment was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 33 publications
2
55
0
2
Order By: Relevance
“…With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered. In particular, long periods of incubation, as well as shear stresses due to centrifugation, increase ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered. In particular, long periods of incubation, as well as shear stresses due to centrifugation, increase ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sperm nuclear DNA damage is not only limited to infertile but also to subfertile patients. Even where the seminal parameters are normal, ejaculates showing sperm with high DNA damage have been reported 10, 11. Moreover, various epidemiological studies reporting the methylation status of imprinted genes of sperm from severely infertile men show a significant risk of imprinting disorders in offspring conceived by IVF and ICSI 18, 19, 20, 21, 22, 23, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Однією з причин порушень у розвитку ембріо-нів на преімплантаційному етапі або вагітності, що вже наступила, є генетичні аномалії у сперматозої-дах -підвищений рівень фрагментації ДНК та хро-мосомні зміни [3][4][5][6][7]. Важливим критерієм нормаль-ного розвитку ембріону є формування бластоцисти високої морфологічної якості на п'ятий день розви-тку [8,9].…”
Section: Zhilkova@feskovcomuaunclassified
“…В останній час значна увага в області репродуктивної медицини приділяється вивченню помилок геному батька. Допоміжні репродуктивні технології (ДРТ), такі, як стандартне екстракорпо-рального запліднення, і, особливо, інтрацитоплаз-матична ін'єкція сперматозоїдів (ІКСІ), дозволяють парам зі значними порушенням показників класич-ної спермограми отримати вагітність, тоді як кілька років тому ці пари були б змушені використовувати донорство сперми для того, щоб отримати дитину [1][2][3][4].Тим не менш, можна обговорювати здатність зразків сперми низької якості до генерації ембріо-нів з нормальним потенціалом розвитку.Однією з причин порушень у розвитку ембріо-нів на преімплантаційному етапі або вагітності, що вже наступила, є генетичні аномалії у сперматозої-дах -підвищений рівень фрагментації ДНК та хро-мосомні зміни [3][4][5][6][7]. Важливим критерієм нормаль-ного розвитку ембріону є формування бластоцисти високої морфологічної якості на п'ятий день розви-тку [8,9].…”
unclassified
“…Spermatic assessment and selection has attracted tremendous attention in recent years. It has been suggested that sperm DNA fragmentation greater than 25.5% is associated with a higher probability of unsuccessful IVF treatment 76. However, sperm selection techniques, such as intracytoplasmic morphologically selected sperm injection, that select spermatozoa at high magnification have not been shown to improve outcomes in studies, including a multicentric randomized controlled trial 76,77.…”
Section: Suggested Strategies To Reduce the Cost Of Ivf Treatmentmentioning
confidence: 99%